İslam aile yapısı açısından Ahzab Suresi’nin tefsiri - Çapan, Ergün (My University, 1992)
Bu çalışmamızda, İslam Dini'nin temel kaynakları olan Kur'an ve Sünnet'in sahabe tarafından nakledildiği, ayrıca bu kaynakların yorumlanmasında onlardan müstağni kalı-namayacağı göz önünde bulundurularak Kur'an'da sahabe konusu incelenmeye çalı-şılmıştır. Tezimiz, bir giriş ve dört ana bölümden oluşmaktadır. Giriş kısmında sahabe kelimesinin lugat ve ıstılah manası, Hadis ve Usul-ü Fıkıhçıların bu kavrama yaklaşım-larından hareket edilerek sahabi statüsünün tesbiti, sahabilerin bilinme yolları ve sayıları üzerinde durduk. Birinci bölümde Kur'an'ın değişik vasıfları ile sahabeyi nasıl anlattığını bu kabilden olarak onların yer yer ikaz edildikleri ve yer yer de övüldükleri yerler vurgulanarak ve onların vasıflarını misallerle ele alarak Kur'an'ın nasıl bir sahabe portresi çizdiğini ele almaya çalıştık. Çalışmamızın ikinci bölümünde Kur'an'da ismen veya işareten kendilerinden bahse-dilen sahabileri ele alarak bunları ne gibi vasıflarla zikrettiği üzerinde durduk. Üçüncü bölümde sahabenin islam dininin neşri adına verdiği mücadeleleri yaptığı savaşları değişik safhaları ile birlikte incelemeye çalıştık. Tezimizin dördüncü bölümünde Kur'an'ın intikalinde sahabenin yerini incelemek üzere tevrat ve incil'in nasıl intikal ettiğinden de bahsederek Kur'an'ın metninin, kıraatının, tefsirinin ve pratik hayata taşınmasında sahabenin yüklendiği misyon üzerinde durduk. Netice itibariyle sahabenin de bir insan olduğu, onların faziletleri olduğu gibi hataları da olabileceği vurgulanmıştır. Fakat, Kur'an'ın kriterlerine göre sahabeye bakıldığında onların iyilik ve güzelliklerinin olumsuzluklarından çok daha fazla olduğu ve üstelik Allah'ın onlardan hoşnutluğunu ifade ederek, cennetleri vaad ettiği belirtilmiştir.

In this dissertation, I attempted to study how the Qur'an deals with the Prophet's Companions. As is known, the Qur'an and Sunna, which are the two basic sources of Islam, were transmitted to the succeeding generations by the Prophet's Companions and therefore it is not possible to be indifferent to them in understanding and interpreting these sources, as well as benefeting from them. This study comprises an introduction and four main chapters. In the Introduction, first I dwelt on what being a Companion means, and then, mainly based on the approach of the Muhaddithun (Traditionists) and Muslim jurists to this term, tried to expound the conditions of being a Companion and the number of the Companions. The first chapter was assigned to how the Qur'an deals with the Companions. Mentioning why and on what occasions the Qur'an admonishes or praises them, I tried to clarify how the Qur'an portrays them. In the second chapter, you will find the Companions the Qur'an mentions by name or alludes to. I particularly dwelt on with which attributes of theirs the Qur'an refers to those Companions. In the third chapter, I tried to explain the efforts and sacrifices the Companions made for the sake of spreading the religion of Islam, including the wars they took part in. As is known, the Companions were the first generation the Qur'an addressed. Having been revealed in their time, the Qur'an was transmitted by them to the succeeding generations. This is the reason why I elaborated how they practiced the Qur'an in their daily individual and collective lives and the mission they performed in interpreting and transmitting it to the generations succeeding them. In doing this, I also mentioned how the Torah and Gospels had been transmitted through generations. Lastly, the Companions were human beings like everybody else. Although they are accepted almost unamiously by the majority of Muslim scholars as the most virtuous of humanity after the Prophets, they may naturally have made some errors or mistakes. However, when considered in the light of the Qur'anic criteria and how the Qur'an deals with them, their virtues weigh much heavier than their mistakes. In its several verses, the Qur'an declares that God was pleased with them and promised them eternal bliss in Paradise.
Keywords: AİLE YAPISI; İSLAM DİNİ - AİLE YAPISI; İSLAM DİNİ - TEFSİR